Association between COVID-19 vaccination and atopic diseases in US adults: A retrospective cohort study - Min Lu; Zixuan Bu; Nana Xiang; Juebo Yu (PLoS ONE, 2025)
COVID-19 Vaccinations are associated with higher allergic reactions risk among adults. However, evidence on whether no vaccinated with COVID-19 vaccine is associated with fewer incidence among individuals with atopic diseases remains limited. This study is to investigate whether COVID-19 Vaccination is associated with increased risk of adult atopic diseases. A cross-sectional survey was conducted using data from the 2021 US National Health Interview Survey (NHIS) that included 29201 respondents aged 18 years or older adults. Multivariable logistic regression was conducted to estimate the association of COVID-19 vaccination and atopic disease. Crude and adjusted odds ratios (aORs) and 95% CIs were estimated. Analysis of the data was performed from October 01, 2023, to January 22, 2024. Of 29201 respondents (mean [SD] age, 52.6 [18.4] years; 13240 [45.3%] male), the US prevalence was 49.6% (unweighted, 95% CI, 49.1%−50.2%) from all years of the2021 NHIS for self-reported hay fever, 13.7% (unweighted,95% CI, 13.3%− 14.1%) for asthma, 10.9% (unweighted, 95% CI,10.1%−11.3%) for skin allergy, 10.0% (unweighted,95% CI, 9.7%−10.4%) for food allergy, and 45.1% (unweighted,95% CI, 45.6%−45.7%) for no COVID-19 vaccination, 6.4% (95% CI, 6.1%−6.9%) for one COVID-19 vaccination, 43.1% (unweighted, 95% CI, 42.6%−43.7%) for two COVID-19 vaccinations, 5.3% (unweighted, 95% CI, 5.1%−5.6%) for more than 2 COVID-19 vaccinations. In multivariable analysis across the 2021 NHIS, COVID-19 vaccinations does not increase the risk of skin a llergy(aOR, 1.03;95%CI, 0.86–1.28; P = 0.135 ), asthma (aOR, 1.05;95%CI,0.98–1.13; P = 0.164), and food allergy (aOR, 1.03;95%CI, 0.95–1.12; P = 0.437) in adults, compared with adults without COVID-19 vaccination; whereas, in patients with COVID-19 vaccination had significantly higher odds of hay fever (aOR, 1.21;95% CI, 1.15–1.27;P < 0.001) compared with adults without COVID-19 vaccination. Further sensitivity and subgroup analysis suggested that the number of COVID-19 vaccinations was associated with newly diagnosed hay fever (aOR, 1.17 95% CI,1.10–1.24; P < 0.001) and asthma (aOR, 1.12 95% CI,1.03–1.27; P = 0.011). In this cross-sectional study, COVID-19 vaccination was associated with higher risk incidence of hay fever, but COVID-19 vaccination was not associated with an increased in incidence risk in skin allergy, asthma and food allergy. The determinants of the association of COVID-19 vaccination with atopic diseases should be identified in the future studies are needed.